High power cladding‐pumped L‐band EDFA with a double‐pass configuration. Issue 9 (September 2015) - Wei, Yizhen; Chen, Feihong; Zhou, Xuefang; Hu, Miao; Li, Qiliang
ABSTRACT A high power broadband cladding‐pumped erbium‐doped fiber amplifier (EDFA) in the long‐wavelength band (L‐band) is proposed and experimentally demonstrated. The L‐band EDFA presented here is based on a double‐pass (DP) configuration, and employs commercially available double‐cladding fiber. An output power over 2 W and an operation wavelength range from 1570 to 1620 nm have been achieved using clad pumping technique in the DP scheme. Compared with the single‐pass structure, obvious improvements on power conversion efficiency and signal gain are obtained while the deterioration of noise figure is also observed. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2186–2189, 2015